Industry Foresight - Kinnunen, Jani (My University, 2002)
This thesis investigates the future of an industry sector. The main purpose is to conduct industry foresight for the case industry. Industry foresight is not a well-constructed theory. A framework for it, is constructed. The purpose of industry foresight is to form a best possible assumption base about the future, ranging as far as twenty years ahead. This is done to serve strategic management decisions such as strategic investment decisions. Motivation to conduct an industry foresight rises fundamentally from a company’s quest for revenues. From a company point of view, it is done to help creating and sustaining a company’s competitive advantage. From a national point of view, competitive advantage of nations is the issue. The methods used in industry foresight include, for instance, econometric forecasting and scenario analysis. These methods are of major importance, as they, together, can utilize both, soft and hard data. This way, all possibly relevant information can be used. Scenario analysis may, e.g., serve as a method for identifying the most meaningful factors within an industry. Scenarios and forecasting methods can also reveal the logic behind these factors, as well as, the cause-effect relations between them. In this thesis, information sources are electronic sources, and the Internet, in general. Sources are selected so that their information can be expected being reliable. Primarily, this means government and institutional databases, economic and financial press, research bodies, and industry specific sources such as industrial associations. Industry foresight is a dynamic evolutionary process. This means that it is an ongoing process. The industry foresight study conducted initially in this thesis, will continue in the future. This is possible, because a support system will be built around the issues identified as relevant for the case industry. This support system is a software agent based information scanning system, which will follow up the crucial issues by collecting related data, by storing it to a system database, and by presenting this information to managers of a company. This agent-based system is presented in the thesis. The major results in this study include: Identifying believably the most crucial issues related to the future of the case industry; Supporting the use of electronic information sources in conducting industry foresight, and the use of Internet for gaining valuable information, in general. The study implies that industry foresight can be conducted for other industries, as well, using electronic data, and software agents as a support tool.
Keywords: Industry foresight; foresight; forecasting; scenario; software agent; fi=Kansantaloustiede|en=Economics|